Adolescents' Pain Coping Profiles: Expectations for Treatment, Functional Outcomes and Adherence to Psychological Treatment Recommendations. (2011) - Claar, Robyn Lewis; Simons, Laura E
Abstract : OBJECTIVES: To explore how adolescents' pain coping profiles relate to their expectations regarding psychological treatment recommendations, and to examine patients' functioning and engagement in psychological treatment three months following a multidisciplinary pain clinic evaluation. METHODS: Adolescents and their parents completed measures of pain coping strategies, treatment expectations, pain ratings, somatic symptoms, school absences and functional disability. Parents also reported whether patients followed through with psychological treatment recommendations. RESULTS: Adaptive copers and their parents were more likely to expect psychological treatments to be helpful; however, at follow-up, there were no significant group differences in patients' participation in psychological treatment. Patients in both groups experienced significantly lower levels of somatic symptoms and functional disability, and had fewer school absences from the initial evaluation to the follow-up. DISCUSSION: The results of the present study identify preliminary clinical implications for the way in which practitioners in multidisciplinary pain clinics present recommendations for psychological treatment to patients and their families.